Lanthanum(III) and neodymium(III) complexes with anti-inflammatory drug sulindac: Synthesis, characterization, thermal investigation using coupled techniques TG-FTIR, and in vitro biological studies - Guerra, Renan B. [UNESP]; de Campos Fraga-Silva, Thais Fernanda [UNESP]; Aguiar, Julia [UNESP]; Oshiro, Paula B. [UNESP]; Holanda, Bruno B.C. [UNESP]; Venturini, James [UNESP]; Bannach, Gilbert [UNESP] (Elsevier, 2020)
New lanthanum(III) and neodymium(III) complexes with the anti-inflammatory drug sulindac (Sul) were synthesized and characterized, and their biological activity was evaluated in vitro. The general formula [Ln(Sul)3]∙nH2O for these complexes was proposed based on thermogravimetry, differential scanning calorimetry, elemental analysis, and complexometric titration using EDTA results. 1H and 13C NMR combined with FTIR data results suggested that the carboxylate groups of all three sulindac molecules are coordinated to the metal ions in a bidentate chelate fashion, with no water molecules (OH2) nor sulfinyl groups (S[dbnd]O) coordinated to the metal center. During thermal decomposition of these complexes, the formation of lanthanide oxyfluorides LaOF and NdO1-xF1+2x, was observed and confirmed by powder X-ray diffraction. TG-FTIR coupled techniques were employed to evaluate volatiles released during thermal decomposition of these complexes and compared with the decomposition pattern of the free sulindac, interestingly providing valuable information about the thermosynthesis of the oxyfluorides as well as the coordination modes of sulindac in the complex. Additionally, cell viability and anti-inflammatory assays were performed with human cells to evaluate the in vitro effect of [Ln(Sul)3]∙nH2O.
Keywords: In vitro; Lanthanum(III); Metallodrug; Neodymium(III); Sulindac; TG-FTIR